Common Measures to Evaluate Flavored Tobacco Products: Recommendations From the Tobacco Centers for Regulatory Science (TCORS) Flavored Tobacco Products Measurement Subcommittee. Issue 1 (27th July 2022) - Bansal-Travers, Maansi; Price, Simani M; Bold, Krysten W; Villanti, Andrea C; Barnes, Andrew; Chansky, Melanie; Krishnan-Sarin, Suchitra; Goniewicz, Maciej L
Abstract: Introduction: Flavored electronic nicotine delivery systems (ENDS) and tobacco products are associated with the initiation and progression of tobacco use. With recent restrictions around flavored products, it is critical to measure both the product and the flavor being used. The Tobacco Centers of Regulatory Science (TCORS) Flavored Tobacco Products Measurement Subcommittee (FTPMS) was established to develop core measures to assess flavored tobacco and ENDS product usage, facilitate data harmonization, replicability, and comparisons across studies. Aims and Methods: The FTPMS used a mixed-method approach to inform the development of recommended measures (first use, current use, reasons for use) to assess tobacco and ENDS product flavors. This included reviewing existing surveys, identifying priority areas, developing new measures, cognitive testing, and finalization of recommended measures. Results: Recommended measures were selected from national surveys (e.g. PATH study) and survey items used in TCORS studies to evaluate first use, current use, and reasons for use of tobacco and ENDS products. Response options were expanded for questions about specific flavors and adapted to allow for assessments relevant to recent federal policies. Supplemental measures were developed for researchers conducting more in-depth research around flavored products. Conclusions: Using an expert consensus process supplemented with cognitive testing, the FTPMS developed recommendations for core and supplemental measures for flavored tobacco and ENDS products. Harmonizing data on these factors for flavored tobacco and ENDS products are critical for researchers and may provide actionable evidence to federal, state, and local regulators and policymakers, as well as support evaluations of policies restricting flavors in these products. Implications: The development of core measures to assess first use, current use, and reasons for use of flavored tobacco and ENDS products will facilitate data harmonization, replicability, and comparisons across studies conducted in different samples or across communities with varying levels of regulation for these products. Use of these standardized measures will allow for a greater understanding of the role of flavors and helps to build a more robust evidence base to inform regulatory decisions to reduce tobacco and ENDS use at the population level.